Analisis Yuridis Money Laundry dalam Penyalahgunaan Rekening Masyarakat Lokal oleh Perusahaan Asing Ilegal di Indonesia - Astrid Fatikhasari; Oci Senjaya (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This research examines the practices of illegal foreign companies operating in Indonesia without permission and exploiting local community bank accounts, which poses a risk of legal violations, particularly in the banking and manufacturing sectors. This research emphasizes the importance of protecting national economic interests thru strengthening legal oversight of foreign company activities. The normative juridical method was used with literature study and analysis of primary legal materials, such as Law No. 1 of 2023 and the Anti-Money Laundering Law. This research found the role of the banking sector in identifying money laundering practices by foreign companies thru local community accounts. The results show that illegal companies exploit the weaknesses in the banking supervision system and the lack of understanding between government agencies. Recommendations include optimizing banking supervision, strengthening inter-agency cooperation, and optimizing the implementation of RegTech.